2018
DOI: 10.1145/3197517.3201397
|View full text |Cite
|
Sign up to set email alerts
|

Learning symmetric and low-energy locomotion

Abstract: Fig. 1. Locomotion Controller trained for different creatures. (a) Biped walking. (b) Quadruped galloping. (c) Hexapod Walking. (d) Humanoid running.Learning locomotion skills is a challenging problem. To generate realistic and smooth locomotion, existing methods use motion capture, finite state machines or morphology-specific knowledge to guide the motion generation algorithms. Deep reinforcement learning (DRL) is a promising approach for the automatic creation of locomotion control. Indeed, a standard benchm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 51 publications
2
124
0
Order By: Relevance
“…We use an identical reward function with w v = 10.0, w a = 0.01, w w = 0.005, w t = 0.2 for all of the presented examples. We also use the mirror symmetry loss proposed in [3] during training of PUP, which we found to improve the quality of the learned locomotion gaits. For controlling the robot to walk in different directions, we rotate the robot's coordinate frame such that the desired walking direction is aligned with the positive x-axis in the robot frame.…”
Section: A Experiments Setupmentioning
confidence: 99%
“…We use an identical reward function with w v = 10.0, w a = 0.01, w w = 0.005, w t = 0.2 for all of the presented examples. We also use the mirror symmetry loss proposed in [3] during training of PUP, which we found to improve the quality of the learned locomotion gaits. For controlling the robot to walk in different directions, we rotate the robot's coordinate frame such that the desired walking direction is aligned with the positive x-axis in the robot frame.…”
Section: A Experiments Setupmentioning
confidence: 99%
“…The key element in these methods is a surrogate objective function that allows for more than one gradient update per data sample. Studies have shown that PPO outperforms TRPO in most cases, which makes it the dominant algorithm used in continuous control [Peng et al 2018a;Yu et al 2018].…”
Section: Reinforcement Learningmentioning
confidence: 99%
“…This technique has been used for learning humanoid climbing movements, where the agent learns 1-, 2-, 3-, and 4-limb movements in order (a limb can be either one of agent's hands or feet) . A recent study proposed a continuous curriculum learning method for providing physical assistance to help the character in locomotion movements [Yu et al 2018].…”
Section: Reinforcement Learningmentioning
confidence: 99%
“…Swimming has been reproduced using a CPG‐based locomotion controller that can generate muscle contraction signals automatically [SLST14]. Recently, Yu et al [YTL18] used reinforcement learning to learn basic motor skills, they applied curriculum learning and used symmetry as a reward. Hu et al [HLL*19] simulated skiing motion given a small set of control inputs by applying skiing techniques.…”
Section: Related Workmentioning
confidence: 99%